Pertanggung Jawaban Korporasi Dalam Tindak Pidana Pencucian Uang - Prakasa, Ragil Surya; Rahmadayanti, Indah; Yolanda , Jelfidha Sukma; Febrianis , Ririn; Farhan , Muhammad Adila; Amanda , Shakira; Pratama , Okta Adi (PUAN INDONESIA, 2024)
The crime of money laundering or what is better known as money laundering is a term that is often heard in various mass media, therefore many understandings have developed regarding the term money laundering. Sutan Remi Sjahdeini emphasized that currently the term money laundering is commonly used to describe efforts carried out by individuals or legal entities to legalize "dirty" money, which is obtained from the proceeds of criminal acts. The term money laundering has been known since 1930 in the United States. The emergence of this term is closely related to laundry companies. This is because at that time the crime of money laundering was carried out by the mafia crime organization through purchasing clothes washing or laundry companies as a place to launder the proceeds of crime, that is where the term money laundering emerged. The legal research method in this research is normative (doctrinal) called legal dogmatics (rechtsdogmatiek). 10 The research activities carried out include inventorying, explaining, interpreting and systematizing and also evaluating the entire positive law (authoritative text) that applies in a particular society or country. by using concepts (understandings), categories, theories, classifications and methods that are formed and developed specifically to carry out all these activities, all of which are directed towards preparing efforts to find a judicial solution to the problem. laws (micro and macro) that may occur in society. In general, the elements of the crime of money laundering are as follows: a. The existence of money (funds) which are illegal or invalid in the eyes of the law. b. There is illicit money (dirty money) which is processed in certain ways through legal (legitimate) institutions so that the perpetrators get large profits. c. With the aim of eliminating traces, so that the source of origin cannot or is very difficult to be identified and traced by legal entities because the profits are not directly spent on goods. The crime of money laundering has been regulated in Law no. 5 of 2010. Types of money laundering are divided into 3 types, namely: The criminal act of money laundering is an act that has quite a big impact on the state, which can be detrimental to the state and the surrounding community. Especially laundering crimes committed by corporations. This of course has a big negative impact, especially in the economic sector. The crime of money laundering in Indonesia is regulated in Law No. 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering.